1998
DOI: 10.1176/ajp.155.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alteration of Personality and Social Behavior by Serotonergic Intervention

Abstract: Central serotonergic function may modulate a dimension of normal personality characterized by reduced negative affective experience and increased affiliative behavior. SSRI administration has significant and detectable effects on these measures even in the absence of baseline clinical depression or other psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
312
0
16

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(348 citation statements)
references
References 39 publications
20
312
0
16
Order By: Relevance
“…Specific serotonin reuptake inhibitors have a therapeutic effect in patients with social phobia (Katzelnick et al 1995;Jefferson 1995); however, this may be related to relief of anxiety rather than direct potentiation of social interaction. In a healthy sample, a selective serotonin reuptake inhibitor, paroxetine, increased affiliative social behavior during a cooperative dyadic task when administered after one week of paroxetine treatment, but not after four weeks of treatment (Knutson et al 1998).As previously described, the main dimensions of human social interaction include affiliative behaviors and also the status-related behaviors of dominance and submission. Thus, it is of interest that serotonin has also been related to dominant and submissive behaviors in monkeys.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Specific serotonin reuptake inhibitors have a therapeutic effect in patients with social phobia (Katzelnick et al 1995;Jefferson 1995); however, this may be related to relief of anxiety rather than direct potentiation of social interaction. In a healthy sample, a selective serotonin reuptake inhibitor, paroxetine, increased affiliative social behavior during a cooperative dyadic task when administered after one week of paroxetine treatment, but not after four weeks of treatment (Knutson et al 1998).As previously described, the main dimensions of human social interaction include affiliative behaviors and also the status-related behaviors of dominance and submission. Thus, it is of interest that serotonin has also been related to dominant and submissive behaviors in monkeys.…”
mentioning
confidence: 63%
“…Most forays into the field of sociopharmacology use either laboratory measures of social interaction, or ask about the global social functioning of the subjects. An example of the former is the study of Knutson et al (1998) in which healthy subjects demonstrated more affiliative behavior in a standardized laboratory dyadic puzzle task after one week of paroxetine treatment, but not after four weeks of treatment. An example of the latter, is the study by Dubini et al (1997) which found that a serotonin reuptake inhibitor, fluoxetine, had a better effect than a noradrenaline reuptake inhibitor, reboxetine, on some aspect of social functioning of depressed patients as assessed by a global measure asking about behavior during and affective responses to social interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included ratings of mood, anxiety, general well being, various aspects of quality of life and personality characteristics. More subtle effects of paroxetine were observed in a subsequent study of normal volunteers (Knutson et al 1998)-a reduction in focal indices of hostility through a decrease in negative affect and an increase in a behavior index of social affiliation. These effects were already present after one week of paroxetine administration.…”
mentioning
confidence: 92%
“…For example, Coccaro and Kavoussi (1997) reported that fluoxetine significantly reduced scores on the Irritability and Aggression subscales of the Overt Aggression Scale of impulsive-aggressive personalitydisordered subjects. In a study of the effects of SSRI treatment on normal volunteers, Knutson et al (1998) found that decreases in assaultiveness and irritability on the Buss-Durkee Hostility Inventory were related to plasma paroxetine levels following 4 weeks of treatment. Alcohol consumption, which has often been associated with impulsivity, has been shown to be reduced by SSRI treatment in human alcoholics (Tiihonen et al 1996) and in a rhesus monkey model of excessive alcohol consumption (Higley et al 1998).…”
mentioning
confidence: 99%